Pengaruh Seleksi Dan Penempatan Kerja Karyawan Terhadap Motivasi Kerja Karyawan PT Radja Angkut Indonesia Tanjung Morawa - Mila Asmawiani Okta (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Work motivation is the main driver of employees to work optimally in achieving company goals. Providing good motivation will create enthusiasm for employees who will improve the performance of each employee. Many factors affect work motivation, including selection and placement. This study was to determine the effect of Job Selection and Placement on Employee Motivation at PT. Radja Angkut Indonesia both partially and simultaneously.This type of research is a quantitative descriptive method. The object of research in this study is the employees of PT. Radja Angkut Indonesia, amounting to 65 people. The sampling technique uses a saturated sampling technique which means the population is the same as the sample. The data analysis technique used is multiple regression analysis.The results showed that partially and simultaneously Job Selection and Placement had an effect on the Employee Motivation of PT. Radja Angkut Indonesia. Companies are advised to maintain or improve the selection process that has been going well by including a certificate/recommendation that remains one of the considerations for prospective workers. Employee placement should be based on academic achievement, employee experience, good physical and mental health, marital status, and age. Determination of these criteria, it is important for the company to get employees who are truly in accordance with the job description. With proper placement, work motivation is expected to increase so that company goals can be achieved.